Evaluation of the use of health care services for non-communicable disease and prevention by children and adolescents in south Italy - Flora Ascione; Diana Cascone; Francesco Napolitano; Gabriella Di Giuseppe (BMC, 2017)
Abstract Background The objectives of this investigation are to evaluate the use of health care services for non-communicable disease and prevention by children and adolescents and to identify the factors linked to the use of health care services. Methods This cross-sectional survey was conducted between December 2014 and January 2015 among 1198 parents of students aged between 5 and 18 years attending 12 selected schools in the geographic area of Salerno and Naples, Italy, using a self-administered questionnarie. Results 68.2% of parents stated that had visited their general practitioner (GP) or family pediatrician (FP) with their child in the last year. 66.2% of children had had at least one visit to a specialist and more than half (54.8%) had had preventive care visits in the last year. The use of preventive care visits within last year was significantly higher amongst female, among those who had visited their GP or FP and among those who had a parent with a college degree or higher. The proportion of emergency department visits and hospital admissions reported were 12.8% and 4.7% respectively. Conclusion This results highlights the need of educational interventions for parents and adolescents in order to increase the utilization of preventive health services.